Precarious Employment and the Law's Flaws: Identifying Regulatory Failure and Securing Effective Protection for Workers - Bernstein, Stephanie; Lippel, Katherine; Tucker, Eric; Vosko, Leah F. (Precarious Employment: Understanding Labour Market Insecurity in Canada, 2006)
This chapter is concerned wtih identifying the many symptoms associated with the inadequacy of workers' protection that the study of precarious employment makes visible. ...[The authors] probe key themes central to regulatory failure in the context of precarious employment, including disparity of treatment between workers in precarious employment and workers with greater security, gaps in legal coverage, the interaction between labour market position and social location, and the lack of compliance and enforcement. --From editor's introductory chapter, p. 37.
Keywords: Labor Unions; Labor laws and legislation; Labor market; Temporary employment